To see or not to see: Investigating the links between patient visibility and potential moderators affecting the patient experience. (September 2016) - Bosch, Sheila J.; Apple, Michael; Hiltonen, Beth; Worden, Elisa; Lu, Yi; Nanda, Upali; Kim, Daejin
Abstract: Perhaps more than ever before, healthcare organizations and designers strive to create patient environments that deliver a superlative patient experience. Outstanding healthcare design requires a delicate balance of interdependent characteristics. This exploratory investigation evaluated whether the staff-to-patient visibility (low versus high) is associated with potential moderating variables that may either enhance or detract from the patient experience. The findings from this investigation demonstrate that patient visibility is associated with improvements among three moderating variables, including increased staff presence in patient rooms, better staff perceptions of their work environment, and reduced unwanted noise reaching patients. The fourth moderator, privacy, was assumed to be higher in the low visibility condition. Although the data related to the patient experience did not allow statistical analysis of patient satisfaction scores, there was a three percent improvement in patient satisfaction in the low visibility environment (specifically overall rating). Although there was an increase in patient fall rates, this difference was not significant. Highlights: Nurses were observed more frequently (p < 0.05) in patient rooms on the post-move unit with greater patient visual privacy. Noise was lower when the patient beds were in the higher privacy, lower staff-to-patient visibility configuration. Patient satisfaction ratings were higher for patients discharged from the higher privacy unit than the lower privacy unit. Although patient falls were somewhat higher in the higher privacy unit, this was not significant (p < 0.05). Staff agreed that the higher privacy unit is better for patients regarding noise and privacy, but not that it is safer.